10 Left atrial adaption in the athletic heart. (5th October 2017) - King, G; Coen, K; Kirk, J; Cormack, CMc; Gannon, S; Coyle, K; Spillane, A; Clarke, J
Abstract : Introduction: As part of a screening programme we performed cardiac Echocardiography on an elite hurling team twice during the last four years and as new players emerged. We used conventional echo parameters plus deformation imaging to assess the athletic heart. We know from previous studies that left ventricular stiffness and compliance is reduced in elite athletes. The aim therefore was to assess the retrograde effect of this on left atrial adaption in competitive athletes compared to controls. Methods: 20 competitive athletes and 20 age and sex-matched sedentary subjects were analysed using conventional Echocardiography and deformation imaging. LA stiffness was determined by measuring peak atrial longitudinal strain (PALS) and peak atrial contraction strain (PACS). Left ventricular (LV) stiffness was also calculated in both groups. Results: LA volume index was greater in athletes as compared with controls (22.6 ± 5.3 vs. 18.6 ± 6.5 mL/m, p < 0.001). LA, PALS and LA PACS were lower in athletes in comparison with controls (p < 0.05, p ≤ 0.001, respectively). The Myocardial stiffness index calculated by E/Ea/ LVEDD was lower in athletes then controls. P< 0.016). Conclusions: Competitive athletes showed a small increase in LA volume and lower LA stiffness compared with controls. Thus, LA enlargement in the setting of the athlete's heart is not associated with increased LA stiffness. These findings further support the premise that reduced LA stiffness and increased LA volume index is associated with reduced left ventricular myocardial compliance.